Plano de monitoramento ambiental para a área da jazida fósforo-uranifera de Itataia, Santa Quitéria/CE - Maranhão, Rosa Maria Ramos (2018)
The chemical element uranium is a mineral of high economic value, it is a strategic energy resource. It is an unstable chemical element and its distribution and dispersion by the earth's crust is associated with the magmatic activity, which facilitates its mobility since the formation of the Primordial Earth. Uranium is an essential constituent of approximately 100 minerals, occurring mainly in Uraninite, UO2. It can also be associated paragenetically to carbonates, phosphates, vanadates, silicates, sulphides and sulphates, with their more pronounced occurrence in granitic rocks, granitic pegmatites and syenites, where the uraninite is distributed. The solubility of uranium is related to its tendency to oxidize in ions of U6 +, its natural mobilization in the environment occurs through the weathering of the rock, by the action of water containing humic substances, which act as powerful agents in the mobilization of metallic ions. Many technologies have been developed to detect pollution and environmental contamination, and legal instruments seek to ensure the minimum safety in mining and industrial enterprises, yet there are climatic factors that can not be overlooked as they increase the risks involved, by the carrying of material, either by the action of the winds, or by action of the surface flow. Risk analysis is an instrument capable of proposing strategies of action in the face of critical situations. The risk involves three points: the cause of the risk, the trajectory and the target. In the case of environmental contamination by radionuclides, we can exemplify: uranium and its descendants, as causes, water as a transport agent, using drainage as a trajectory and contamination of soils and groundwater, with a direct impact on human health, in that analysis is the target. Uranium and phosphate are elements of strategic economic interest, are considered a source of wealth and social development, so there is no argument for not being exploited, what is proposed is that the negative impacts are anticipated and the necessary adjustments are made to avoid potential disasters. In this way the perception of the relations of the climate, rainfall, lithology, geology and drainage, in the formation of the reliefs, facilitate in the understanding of the environments and the factors that make them more or less unstable. The presence of springs contributes to the constant transport of material and contributes intensely to the morphogenesis and morphometry of environments influenced by erosive processes. Laminar erosion is very common in semi-arid environments due to the type of drainage characteristic of crystalline environments. Remote sensing applied to the geomorphology allows to recognize the active processes, since they reveal aspects related to morphogenesis, making it possible to extract the morphometric variables, such as altitude, slope orientation, slope orientation, surface flow direction, useful for monitoring related research risks related to the movement of masses or contamination of soil and water resources. Flow modeling is also an important analytical tool for geotechnology. This research deals with the recognition of the natural dispersion of radionuclides in the environment, used geotechnologies to recognize the active processes and the areas susceptible to contamination in the Riacho Cunha Moti subbasin. It is hypothesized that the activities foreseen in the proposed thesis are based on the premise that there is an intrinsic correlation between the materials and processes occurring in the Riacho Cunha Moti hydrographic subbasin and the dispersion of radioactive contaminants in the natural environment, impact on water resources and human health. This thesis proposes an environmental monitoring plan, with a view to the control of the instances and processes involved in the various mining spheres: Industrial, Social and Ecological, serving as an instrument for decision support, since it is built on an integrated analysis, under the paradigm of object orientation.